Giraffe (Giraffa camelopardalis) social networks in areas of contrasting human activity and lion density. (6th August 2019) - Muller, Zoe; Cuthill, Innes C.; Harris, Stephen
Abstract: The adaptive value of close social bonds and social networks has been demonstrated in a variety of vertebrate taxa. While the effect of predators on populations is well established, disturbance by humans is increasingly being identified as affecting the behaviour and reproductive success of animals and can have significant impacts on their survival. We used a concurrent analysis of two adjacent giraffe Giraffa camelopardalis populations in Kenya to determine whether human activities and high predation affected their social networks. One study site was a premier tourist destination with a high volume of human activity in the form of tourist traffic and lodge infrastructure, alongside a high density of lions which preferentially prey on giraffe calves; the other was a private wildlife conservancy with minimal human activity and no lion population. Giraffes in both networks showed preferred associations and avoidances of other individuals, which were independent of space use. Bond strength was lower in the population exposed to high levels of human activity and lions, and the network had lower density and clustering, and shorter path lengths, suggesting that it was more fragmented. We suggest that human activity and predator density may influence the patterns of social interactions in giraffes and highlight the importance of understanding the impact of tourism and management on the survival and success of wild animal populations.